2013
DOI: 10.4187/respcare.02255
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Adult Respiratory FailureDiscussion

Abstract: Extracorporeal membrane oxygenation (ECMO) is a form of cardiopulmonary bypass that is a mainstay of therapy in neonatal and pediatric patients with life threatening respiratory and/or cardiac failure. Historically, the use of ECMO in adults has been limited, but recent reports and technological advances have increased utilization and interest in this technology in adult patients with severe respiratory failure. As ECMO is considered in this critically ill population, patient selection, indications, contraindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 91 publications
0
33
0
3
Order By: Relevance
“…There are no published studies to date regarding the success of this strategy in adults who suffer immediate cardiac arrest subsequent to massive aspiration and recovery in this setting is highly unlikely. Based on studies of ECMO for ARDS in adults, 2628 a theoretical benefit for patients who subsequently develop ARDS secondary to intraoperative aspiration may exist. The decision to implement ECMO in this situation depends on the availability of ECMO, the reversibility of the underlying disease process and the severity of associated comorbid conditions.…”
Section: Management Of Acute Intraoperative Aspirationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no published studies to date regarding the success of this strategy in adults who suffer immediate cardiac arrest subsequent to massive aspiration and recovery in this setting is highly unlikely. Based on studies of ECMO for ARDS in adults, 2628 a theoretical benefit for patients who subsequently develop ARDS secondary to intraoperative aspiration may exist. The decision to implement ECMO in this situation depends on the availability of ECMO, the reversibility of the underlying disease process and the severity of associated comorbid conditions.…”
Section: Management Of Acute Intraoperative Aspirationmentioning
confidence: 99%
“…The decision to implement ECMO in this situation depends on the availability of ECMO, the reversibility of the underlying disease process and the severity of associated comorbid conditions. 28 …”
Section: Management Of Acute Intraoperative Aspirationmentioning
confidence: 99%
“…Solunumsal diyaliz olarak da isimlendirilen yöntem ile çift lümenli kanül venovenöz (VV) ya da venoarteryel (VA) olarak hastaya yerleştirilmektedir. Hastadan gaz değişim ünitesine belli akım hızında kan akışı sağlanarak kan oksijenlendirilmekte, oksijenlenmiş kan hastaya gönderilmektedir (7). Hemodinamik olarak destek gereken olgularda venoarteryel kanülasyon öne-rilmektedir (6).…”
Section: Discussionunclassified
“…Hastamızda izlemi sırasında önemli bir komplikasyon izlenmedi. Solunum yetmezliği olan olgularda %70'in üzerinde ECMO başarısı bildirilmiştir (7). ECMO başarı-sında doğru uygulama, uygun hasta seçimi, uygun takip ve zamanlama önemlidir.…”
Section: Discussionunclassified
“…ECMO in severe acute respiratory distress syndrome allows lungprotective ventilation by allowing rest ventilator settings and externally controlling gas exchange. 103 Although previous trials had negative results, recent improvements in membrane technology and catheter systems have led to renewed interest. 104 A multicenter randomized controlled trial showed benefit in patients referred to an ECMO center for "consideration of ECMO" compared with standard therapy at the referring center.…”
Section: Rescue Oxygenation Strategies In Acute Respiratory Distress mentioning
confidence: 99%